Investigating acoustic startle habituation and prepulse inhibition with silent functional MRI and electromyography in young, healthy adults - Naysmith, Laura F.; O’Daly, Owen; Solana, Ana Beatriz; Wiesinger, Florian; Hill, Simon; Williams, Steven C. R.; Kumari, Veena (Frontiers in Human Neuroscience, 2024)
Introduction: Startle habituation and prepulse inhibition (PPI) are distinct measures of different sensory information processes, yet both result in the attenuation of the startle reflex. Identifying startle habituation and PPI neural mechanisms in humans has mostly evolved from acoustic-focused rodent models. Human functional magnetic resonance imaging (fMRI) studies have used tactile startle paradigms to avoid the confounding effects of gradient-related acoustic noise on auditory paradigms and blood-oxygen-level-dependent (BOLD) measures. This study aimed to examine the neurofunctional basis of acoustic startle habituation and PPI in humans with silent fMRI. Methods: Using silent fMRI and simultaneous electromyography (EMG) to measure startle, the neural correlates of acoustic short-term startle habituation and PPI [stimulus onset asynchronies (SOA) of 60ms and 120ms] were investigated in 42 healthy adults (28 females). To derive stronger inferences about brain-behaviour correlations at the group-level, models included EMG-assessed measures of startle habituation (regression slope) or PPI (percentage) as a covariate. A linear temporal modulator was modelled at the individual-level to characterise functional changes in neural activity during startle habituation. Results: Over time, participants showed a decrease in startle response (habituation), accompanied by decreasing thalamic, striatal, insula, and brainstem activity. Startle habituation was associated with the linear temporal modulation of BOLD response amplitude in several regions, with thalamus, insula, and parietal lobe activity decreasing over time, and frontal lobe, dorsal striatum, and posterior cingulate activity increasing over time. The paradigm yielded a small amount of PPI (9-13%). No significant neural activity for PPI was detected. Discussion: Startle habituation was associated with the thalamus, putamen, insula, and brainstem, and with linear BOLD response modulation in thalamic, striatal, insula, parietal, frontal, and posterior cingulate regions. These findings provide insight into the mediation and functional basis of the acoustic primary startle circuit. Instead, whilst reduced compared to conventional MRI, scanner noise may have disrupted prepulse detection and processing, resulting in low PPI and impacting our ability to map its neural signatures. Our findings encourage optimisation of the MRI environment for acoustic PPI-based investigations in humans. Combining EMG and functional neuroimaging methods shows promise for mapping short-term startle habituation in healthy and clinical populations.